Cultivated bacterial diversity associated with the carnivorous plant Utricularia breviscapa (Lentibulariaceae) from floodplains in Brazil - Lima, Felipe Rezende; Ferreira, Almir José; Menezes, Cristine Gobbo [UNESP]; Miranda, Vitor Fernandes Oliveira [UNESP]; Dourado, Manuella Nóbrega; Araújo, Welington Luiz (Springer Nature, 2018)
Carnivorous plant species, such as Utricularia spp., capture and digest prey. This digestion can occur through the secretion of plant digestive enzymes and/or by bacterial digestive enzymes. To comprehend the physiological mechanisms of carnivorous plants, it is essential to understand the microbial diversity related to these plants. Therefore, in the present study, we isolated and classified bacteria from different organs of Utricularia breviscapa (stolons and utricles) and from different geographic locations (São Paulo and Mato Grosso). We were able to build the first bacterium collection for U. breviscapa and study the diversity of cultivable bacteria. The results show that U. breviscapa bacterial diversity varied according to the geographic isolation site (São Paulo and Mato Grosso) but not the analyzed organs (utricle and stolon). We reported that six genera were common to both sample sites (São Paulo and Mato Grosso). These genera have previously been reported to be beneficial to plants, as well as related to the bioremediation process, showing that these isolates present great biotechnological and agricultural potential. This is the first report of an Acidobacteria isolated from U. breviscapa. The role of these bacteria inside the plant must be further investigated in order to understand their population dynamics within the host.
Keywords: Aquatic microbiota; Microbial communities; Microbial ecology; Utricularia breviscapa